Physiological Processes Modulated by the Chloride-Sensitive WNK-SPAK/OSR1 Kinase Signaling Pathway and the Cation-Coupled Chloride Cotransporters - Murillo-de-Ozores, Adrián Rafael; Chávez-Canales, María; de los Heros, Paola; Gamba, Gerardo; Castañeda-Bueno, María (Frontiers in Physiology, 2020)
The role of Cl- as an intracellular signaling ion has been increasingly recognized in recent years. One of the currently best described roles of Cl- in signaling is the modulation of the With-No-Lysine (K) (WNK) - STE20-Proline Alanine rich Kinase (SPAK) / Oxidative Stress Responsive Kinase 1 (OSR1) - Cation-Coupled Cl- Cotransporters (CCCs) cascade. Binding of a Cl- anion to the active site of WNK kinases directly modulates their activity, promoting their inhibition. WNK activation due to Cl- release from the binding site leads to phosphorylation and activation of SPAK/OSR1, which in turn phosphorylate the CCCs. Phosphorylation by WNKs-SPAK/OSR1 of the Na+-driven CCCs (mediating ions influx) promote their activation, whereas that of the K+-driven CCCs (mediating ions efflux) promote their inhibition. This results in net Cl- influx and feedback inhibition of WNK kinases. A wide variety of alterations to this pathway have been recognized as the cause of several human diseases, with manifestations in different systems. The understanding of WNK kinases as Cl- sensitive proteins has allowed us to better understand the mechanistic details of regulatory processes involved in diverse physiological phenomena that are reviewed here. These include cell volume regulation, potassium sensing and intracellular signaling in the renal distal convoluted tubule, and regulation of the neuronal response to the neurotransmitter GABA.